The Possibility of Developing and Management of Direct Sales in the Conditions of Electronic Economy - Ewa KORELESKA (Communications of International Proceedings, 2020)
The aim of this study is to present development possibilities of direct sales of food products under the conditions of electronic economy. Secondary data was obtained from - CEBOS reports from the years 2002 to 2020, as well as from the Central Statistical Office and primary data were obtained from three interviews with the Internet users for better interpretation of the secondary data. A case study method was also employed which involved analyzing Rural e-box’ project (2020). For this purpose, secondary and primary data obtained from an interview with the project manager were. It was found that a vast number of the Polish Internet users (85%) do used the Internet for shopping. However, as compared to other countries, Poles use this form of sale much more rarely (19 position among 29 European countries in 2020). Purchasing food via the Internet is not yet very popular among the Internet users (7% of Internet users), though it is worth noting that for the last year it has gained in importance. In the opinion of the Internet users it was caused by a wider assortment of products offered by online stores and manufactures and better equipment and access to the Internet and the pandemic. It seems that the concepts of the type of Rural e-box which are of regional character with the use of modern internet, informatic technologies, modern management methods reduce the concerns about the food quality and its delivery time, are very likely to find followers in Poland.
Keywords: Internet; management; direct sales; distribution; electronic economy; food; organic food; online shopping